1984
DOI: 10.1159/000233569
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the IgE Antibody Response by Glutaraldehyde-Modified Ovalbumin: Dissociation between Loss of Antigenic Reactivity and Ability to Induce Suppression

Abstract: Ovalbumin (OA) was substituted with glutaraldehyde (GA) at various GA:OA ratios and several preparations were isolated by gel filtration according to molecular weight. Two GA-substituted but unpolymerized preparations (OA1-L and OA1H) and 3 polymerized preparations of increasing molecular weight (OA4, OA175 and OA-POL) were obtained and were assessed for their ability to react with IgG and IgE antibodies directed against the native OA molecule, as well as for their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thus, antigen presentation by hepatic nonparenchymal accessory cells (36) supports proliferation of long term Thl and not Th2 clones, while T cell lines derived using hapten-modified Langerhans cells yield almost exclusively Th2-like lines (37). OAPOL differs markedly from native OA in terms of its antigenicity at the B cell level, retaining only 0.5-5% of its capacity to be bound by anti-OA antibodies (22). This suggests that the B cell may play a markedly smaller role than other APC in the presentation of OAPOL and may be responsible in part for the preferential synthesis of IFN-y in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, antigen presentation by hepatic nonparenchymal accessory cells (36) supports proliferation of long term Thl and not Th2 clones, while T cell lines derived using hapten-modified Langerhans cells yield almost exclusively Th2-like lines (37). OAPOL differs markedly from native OA in terms of its antigenicity at the B cell level, retaining only 0.5-5% of its capacity to be bound by anti-OA antibodies (22). This suggests that the B cell may play a markedly smaller role than other APC in the presentation of OAPOL and may be responsible in part for the preferential synthesis of IFN-y in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although promising in terms of enhanced safety, these preparations failed to demonstrate marked decreases in IgE production and their mechanism of action remains unknown . It is unclear if this reflects differences in the modification approaches used and thus the heterogeneity of the resultant products (22) or more basic differences in regulatory mechanisms which govern antibody formation in human and murine systems .…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the extent of antigen-specific IgE after OVA-MRBC immunization is below the level that induces IgE-mediated shock. The OVA-MRBC conjugate has an ad vantage compared with the previously reported GA-polymerized antigen because the GA-polymerized antigen loses its major antigenic determinants [8] and could not be ex pected for use as an immunogen. In agreement with our findings, Relyveld and Ben-Efraim [9] have reported that the coupling of tetanus toxin to L1210 leukemia cells or to normal rabbit peripheral lymphocytes using the GA method induced antitetanus toxin antibody in experimental animals suggesting that antigens other than OVA are applicable to this system although they provided no information on IgE antibody synthesis.…”
mentioning
confidence: 99%